Pond mitigation in dissolved and particulate pesticide transfers: Influence of storm events and seasonality (Auradé agricultural catchment, SW-France). (15th October 2022) - Chaumet, Betty; Probst, Jean-Luc; Payré-Suc, Virginie; Granouillac, Franck; Riboul, David; Probst, Anne
Abstract: In agricultural headwater catchments, wetlands such as ponds are numerous and well known to partly dissipate contamination. Most of the pesticides are transferred from soils to the aquatic environment during flood events. This study reports the annual/seasonal behaviour of 6 pesticides (metolachlor, boscalid, epoxiconazole, tebuconazole, aclonifen and pendimethalin) in such an environment. Because it is rarely considered, the study focussed on the high frequency of the distribution of pesticides between dissolved and particulate phases, as well as the main controlling factors of their upstream-downstream transfer. The pond removal rate was calculated to evaluate the wetland efficiency in pesticide mitigation. We conducted a one-year high frequency hydrochemical survey, with particular emphasis on flood events, in the upper Auradé catchment (SW-France), an area of long-term conventional agriculture on highly erosive carbonated soils. The inlet and outlet of the pond were instrumented for water level measurements and water sampling. The highest concentrations were observed for tebuconazole and, in general, the presence of the molecules during the year depended on the season. The pond showed satisfactory efficiency in pesticide attenuation for the six molecules considered, although the removal rate depended on the molecule and the bearing phase (from 28.4% for boscalid to 89.4% for aclonifen in the dissolved phase and from 22.1% for pendimethalin to 96.8% for metolachlor in the particulate fraction). Interestingly, the more hydrophilic the molecule (low LogKOW ), the more efficient the pesticide removal rate was for its particulate fraction, and the opposite for hydrophobic molecules (high LogKOW ). Flood events carried a large amount of Total Suspended Solid (TSS) bearing hydrophobic molecules from a major legacy of upper catchment soils, although 52% of the pesticides were transported by the dissolved fraction. Significant resuspension of TSS from the pond was evidenced by the annual mass balance with four tons of TSS released, while the positive rate of pesticide removal involved other effective mechanisms such as exchange and complexation. Although these constructed wetlands may be beneficial for pesticide mitigation, the results highlighted the need for improved land management in the upstream catchment during the different seasons to avoid bare soils that pose a risk of high surface water contamination, especially due to the presence of hydrophobic molecules in combination with a high erosive context. Graphical abstract: Image 1 Highlights: The positive mass balance indicates a pond mitigation for six considered molecules. Pesticide removal rate is higher in the dissolved phase than in the particulate phase. Flood events are the main pesticide transport pathway and environmental risk. Hydrophobicity plays a major role in pesticides fate in wetlands complex systems.